Main directions for energy use of biomass in Romania - Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Energy is an area of strategic and vital importance for Romania's economic development. At national level there is a wide activity of using biomass for the production of electricity and heat, determined by the requirements of the European Union's energy policy to reduce CO2 emissions. The availability of biomass resources has made it an attractive source of renewable energy, with the potential to provide economical and cost-effective energy. The paper presents a review of directions and policies on bioenergy and energy production through the use of biomass.
Keywords: Q16; Q42; Q48; 330; biomass resources; renewable energy; energy policies